Guided Reading Strategy Improves Reading Comprehension in Grade IV Students: Strategi Membaca Terbimbing Meningkatkan Pemahaman Membaca pada Siswa Kelas IV - Juliana, Fakhira; Guswita, Reni; Habibie, Zulqoidi R. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Reading comprehension is a crucial literacy skill that supports academic success and lifelong learning. Specific Background: However, many elementary students still struggle to identify main ideas, understand vocabulary, and summarize texts, which hinders their broader learning development. Knowledge Gap: Previous studies have shown the potential of the Guided Reading strategy, but limited research has adapted this method to rural elementary school contexts with heterogeneous student abilities and limited resources. Aims: This study aimed to investigate the effectiveness of Guided Reading in improving reading comprehension among fourth-grade students at SD Negeri 32/II Muara Bungo. Results: Using a Classroom Action Research (CAR) design across two cycles, findings revealed significant improvements: mastery increased from 45.4% at pre-action to 63.6% and 72.7% in cycle I, and further to 77.2% and 90.9% in cycle II, reaching the “very good” category. Novelty: The study introduced contextualized reading materials and collaborative discussion approaches tailored to students’ local environment, differentiating it from prior implementations. Implications: These findings highlight Guided Reading as an effective and adaptable strategy to enhance literacy skills in resource-constrained schools, contributing to national literacy goals and offering a replicable model for similar contexts.Highlight : Guided Reading Strategy effectively improves reading comprehension skills. Students’ learning outcomes increased from pre-cycle to cycle II. Pre-reading, during-reading, and post-reading stages were applied systematically. Keywords : Skills, Reading Comprehension, Guided Reading Strategy, Students, Literacy